Potential for serodiagnosis of indonesian leprosy patients by detecting antibodies against LID-1 - Nanny Herwanto; S. Sawitri; Cita Rosita Sigit Prakoeswa; Shinzo Izumi; Malcom S. Duthie; Indropo Agusni (PAGEPress Publications, 2019)
Leprosy is caused by Mycobacterium leprae infection and remains a major public health problem in many areas of the world. The Leprosy IDRI Diagnostic (LID)-1 antigen has demonstrated potential to improve the diagnostic capacity of local health centers and aid the development of strategies for the eventual control and elimination of leprosy from endemic areas. The diagnostic capacity of LID-1 has not yet, however, been studied in Indonesia. Objective: To determine the proportion of Indonesian leprosy patients that have circulating antibodies against LID-1. Sera from thirtyfive leprosy patients from Surabaya, Indonesia were evaluated using an Enzyme Linked Immunosorbent Assay (ELISA) detecting IgG antibodies against the LID-1 antigen. Anti-LID-1 antibody levels correlated with both the clinical form of leprosy and the bacterial index (BI). LID-1-specific IgG responses were higher in multibacillary (MB) than in paucibacillary (PB) leprosy patients. Our data indicate that the detection and measurement of serum IgG against LID-1 could be an effective tool for use in control programs in various states and municipalities in Indonesia.